PENGARUH MOTIVASI DAN SELF EFFICACY TERHADAP KINERJA GURU DIMODERASI GAYA KEPEMIMPINAN TRANSFORMASIONAL (Studi pada Guru-Guru SMP Negeri Se-Kecamatan Bojong Kabupaten Pekalongan) - Liana, Lie; Rijanti, Tristiana (Proceeding SENDI_U, 2016)
This research aimed to know the influence of motivation and self-efficacy on teacher performancemoderated by transformational leadership style to the teachers of State Junior High School in Bojong Sub Districtof Pekalongan Regency. This research used field research with quantitative approach. The Population in thisresearch was teachers who teach in State Junior High School in Bojong Sub District of Pekalongan Regency thatnumber106 people and take all the population. Based on the instrument test that was validity test & reliability testacquired valid & reliabel indicators for further analysis. Based on the F test showed that the model reasonable tofurther analysis. The R2 test showed the contribution independent variable to the dependent variable. Thehyphotesis test used t test by MRA. The result of the research showed that motivation has no influence on theteacherâs performance, self-efficacy influences positively on teacherâs performance, the transformationalleadership style influences positively on teacher performance, the transformational leadership style does notmoderate the influence of motivation on teacher performance and transformational leadership style has weaken theinfluence of self-efficacy on teacher performance.Keywords: motivation, self-efficacy, transformational leadership style, and teacher performance.